PENGARUH PIJAT REFLEKSI TANGAN TERHADAP SKALA INTENSITAS NYERI PADA PASIEN POST SEKSIO SESAREA DI BRSU TABANAN - Murni, Jati (Coping: Community of Publishing in Nursing, 2014)
Pain post surgery in patients with post caesarean section occurr because the inflammatory response in the area of ??operations. The hands reflexology massage provides relaxation and minimizes sympathetic nervous activity in the autonomic nervous system. Adrenaline and cortisol will decrease strees of patiens and it can improve concentration and calm feeling. This study aimed to determine the effect of hands reflexology for pain intensity scale on post sectio caesarea patients in BRSU Tabanan. This research method is Quasy-experimental design with pre-test and post-test with control group design. Sample consist of 30 post which are sectio caesarean patients selected with purposive sampling technique, divided become two groups, which are the control group and the treatment group. The treatment group was given the hands reflexology massage for 30 minutes. Both of groups was measured by using a scale of numeric (0-10) for examine pre-test and post-test pain intensity scale. Research results mean of decreasing of pain intensity at 5,33 in post-test treatment group, and at 6,60 in post-test control group. Based on analysis by the independent sample t-test, this difference is statistically significant, with value of “t” equal to 2, and a value of p-value 0,026, which means that there is effects of hands reflexology for pain intensity scale on post sectio caesarea patients in BRSU Tabanan.